Diversities in presentations of extrapulmonary tuberculosis. (28th February 2013) - Neelakantan, Shiba; Nair, Preeti P; Emmanuel, Roby V; Agrawal, Kavita
Abstract : The incidence of extrapulmonary tuberculosis (EPTB) has been increasing worldwide over the last few years. Tuberculous lymphadenitis is the most common form of the disease and is reported to occur in 25–60% of all EPTB cases. It is commonly seen in the cervical lymph nodes, but may also be in the larynx, pharynx, parotid and rarely, in the sinuses and petrous bone. The posterior triangle, supraclavicular and jugular nodes are most frequently affected. They are usually unilateral, although diffuse adenopathy may occur. TB involving cervical lymph nodes represents 50% of extrapulmonary TB. A series of six cases of tuberculous lymphadenitis with varying clinical features is documented here to alert one of its prevalence in developing countries.